Constant volume ring shear test for sand. - Infante Sedano, Julio Angel. (University of Ottawa (Canada), 1999)
A ring shear device was designed to permit constant volume tests to be performed on granular materials. Constant volume ring shear tests can be used to simulate undrained conditions of shearing. The very large deformations allowed by the ring shear device are well suited to determine the steady-state strength of granular material. The steady state strength is an important parameter in evaluating the stability of sand deposits against flow sliding. The main contributions of this study are as follows: (1) Tools and methods were developed to prepare annular samples of granular materials. (2) Tools and methods were developed to verify the quality of the samples prepared. (3) Tests on Unimin 2010 quartz sand showed that for this material, the steady state shear strength is independent of the presence of water, the rate of shear, and the fines content. (4) There is good agreement in the steady state line obtained from constant load and constant volume ring shear tests with that obtained from triaxial tests. (5) The constant volume ring shear test provides a lower steady-state friction angle than the undrained triaxial test.
Keywords: Engineering, Civil.